The Influence of Internal Control and Organizational Culture on The Tendency of Accounting Fraud with Honesty as a Moderating Variable - Mega Nadia Aprilia; Anak Agung Gde Putu Widanaputra (E-Jurnal Akuntansi, 2024)
The purpose of this study is to examine the influence of honesty as a moderating variable of internal control and organizational culture on accounting fraud tendencies. This research was conducted at BPD in Badung Regency with a total sample of 75 respondents using a purposive sampling technique. The data analysis technique used is moderated regression analysis. The results showed that honesty is able to moderate the effect of internal control and organizational culture on accounting fraud tendencies. The implication of this research is that it is expected to be able to provide additional knowledge and information related to the influence of internal control, organizational culture,and honesty on accounting fraud tendencies.